Benefits and Risks of a Staged‐Bilateral VIM Versus Unilateral VIM DBS for Essential Tremor. Issue 6 (14th June 2022) - Prakash, Prarthana; Deuschl, Guenther; Ozinga, Sarah; Mitchell, Kyle T.; Cheeran, Binith; Larson, Paul S.; Merola, Aristide; Groppa, Sergiu; Tomlinson, Tucker; Ostrem, Jill L.
ABSTRACT: Background: Despite over 30 years of clinical experience, high‐quality studies on the efficacy of bilateral versus unilateral deep brain stimulation (DBS) of the ventral intermediate (VIM) nucleus of the thalamus for medically refractory essential tremor (ET) remain limited. Objectives: To compare benefits and risks of bilateral versus unilateral VIM DBS using the largest ET DBS clinical trial dataset available to date. Methods: Participants from the US St. Jude/Abbott pivotal ET DBS trial who underwent staged‐bilateral VIM implantation constituted the primary cohort in this sub‐analysis. Their assessments "on" DBS at six months after second‐side VIM DBS implantation were compared to the assessments six months after unilateral implantation. Two control cohorts of participants with unilateral implantation only were also used for between‐group comparisons. Results: The primary cohort consisted of n = 38 ET patients (22M/16F; age of 65.3 ± 9.5 years). The second side VIM‐DBS resulted in a 29.6% additional improvement in the total motor CRST score ( P < 0.001), with a 64.1% CRST improvement in the contralateral side ( P < 0.001). An added improvement was observed in the axial tremor score (21.4%, P = 0.005), and CRST part B (24.8%, P < 0.001) score. Rate of adverse events was slightly higher after bilateral stimulation. Conclusions: In the largest ET DBS study to date, staged‐bilateral VIM DBS was a highly effective treatment for ET with bilateral implantation resulting in greater reduction in total motor tremor scores when compared to unilateral stimulation alone.